Restriction of work in retail on weekends and holidays (Polish experience) - Jakub Stelina (Правоприменение, 2019)
The subject of the article is legal regulation of work in retail on Sundays and holidays in Poland and in the European Union.The main aim of the article is to confirm or disprove the hypothesis that restrictions on work in retail on Sundays are not due to the needs of the economy and law, but due to the political situation in Poland, and therefore, although these restrictions are not rejected by the Polish society, they can be revised easily after the elections.The methodology of the study includes analysis, synthesis, description, interpretation as well as particular academic legal methods (historical overview, comparative analysis of legislation, formal‐legal method, interpretation of legal acts).The main results and scope of their application. The article discusses legal restrictions in Poland concerning work on Sundays and public holidays, especially in retail. General rules concerning work on these days are set in the Polish Labor Code in accordance with the EU legislation. Recently, a law was passed in Poland introducing the restriction of employment in retail outlets on Sundays and other public holidays. This law was entered into force on March 1, 2018 with two years transition period. After transition period a total ban on working on Sundays and holidays in shops and other retail (except some special sales places, such as post offices, ticket offices etc.) will be established. Thus, discussions and disputes over the years, which have been going on almost from the very beginning of the systemic transformation, have been closed for many years. The author of the article presented a systematic analysis of legislation and various problems on the example of Poland and the European Union. The limitations on employment on Sundays are the protective measures established by labour law provisions. They combine the function of securing rest to employees with their role of a method allowing the society to celebrate certain days due to lay or religious reasons. Macroeconomic effects of the restrictions of work in retail on Sundays are not known yet. Nevertheless, it seems that the apocalyptic visions of the condition of Poland’s economy, free of commerce made on Sundays (such as a dramatic drop in GDP or a rapid growth of unemployment) are rather far from reality.Conclusions. The Polish law restricting work on Sundays and public holidays in retail is not totally rejected by Polish society, but it may be subject to further changes. It depends on what political forces will exercise power in Poland.